Fenomena laki-laki Gen Z takut menikah akibat standarisasi finansial tinggi oleh calon wanita (Analisis Tafsir Q.S An -Nur ayat 32) - Noer Zaini Khalis; Heri Firmansyah (Pascasarjana Institut Agama Islam Sunan Giri Ponorogo, 2026)
The phenomenon of reluctance or fear of marriage (marriage phobia) among Generation Z men in Indonesia is increasingly on the rise. One of the main determining factors is psychological pressure due to the high financial standards set by prospective female partners or their families. This often clashes with the economic reality of Gen Z, who are at the early stages of their careers, causing anxiety about their inability to meet material expectations. This study uses a qualitative method with a library research approach. Analysis was conducted using interpretative and thematic methods on Q.S. An-Nur verse 32 as an analytical tool to address the issue of financial anxiety. Data were collected from classical and contemporary exegesis literature, as well as sociology journals related to Gen Z marriage behavior. This study aims to reconstruct understanding regarding Allah's assurance for those who intend to marry in order to protect their personal dignity. The analysis results show that Q.S. An-Nur verse 32 conveys an optimistic message that marriage is a gateway to sustenance, not a burden that must wait for absolute financial stability. This verse emphasizes that poverty is not a barrier to the legitimacy of marriage, but rather an encouragement for society to help facilitate the process. This interpretation offers a theological solution for Gen Z men to shift their focus from financial fears to mental preparedness and measured efforts, while also serving as a critique of the shift in marriage values that tend to be materialistic in the modern era.